Ototoxicity and Teprotumumab. (August 2022) - Highland, Julie; Gordon, Steven; Reddy, Deepika; Patel, Neil
Objectives: Teprotumumab, a novel monoclonal antibody, targets the insulin-like growth factor 1 (IGF-1) receptor. IGF-1 receptors, found in muscle and fat adjacent to the eye and implicated in Graves Ophthalmopathy, are also in the cochlea. In clinical trials, 5 participants reported self-limited audiologic symptoms but there are no objective data in the literature. The aim of this report is to describe one of the first known cases of teprotumumab-induced irreversible sensorineural hearing loss. Methods: Case report at a tertiary referral center Results: A 61 year old female with Graves ophthalmopathy presented with bilateral hearing loss, sound distortion, and tinnitus following treatment with teprotumumab. Audiogram showed mild sloping to moderately-severe sensorineural hearing loss. Repeat audiometry obtained 4 months after cessation of teprotumumab and treatment with oral corticosteroids was unchanged. Conclusions: This is one of the first descriptive cases of ototoxicity resulting in irreversible sensorineural hearing loss in the setting of treatment with teprotumumab. Periodic audiologic evaluations should be recommended to patients on teprotumumab.